Rapid Activation of Transforming Growth Factor β–Activated Kinase 1 in Chondrocytes by Phosphorylation and K63‐Linked Polyubiquitination Upon Injury to Animal Articular Cartilage. Issue 3 (27th February 2017) - Ismail, Heba M.; Didangelos, Athanasios; Vincent, Tonia L.; Saklatvala, Jeremy
Abstract : Objective: Mechanical injury to cartilage predisposes to osteoarthritis (OA). Wounding of the articular cartilage surface causes rapid activation of MAP kinases and NF‐κB, mimicking the response to inflammatory cytokines. This study was undertaken to identify the upstream signaling mechanisms involved. Methods: Cartilage was injured by dissecting it from the articular surface of porcine metacarpophalangeal (MCP) joints or by avulsing murine proximal femoral epiphyses. Protein phosphorylation was assayed by Western blotting of cartilage lysates. Immunolocalization of phosphorylated activating transcription factor 2 (ATF‐2) and NF‐κB/p65 was detected by confocal microscopy. Messenger RNA (mRNA) was measured by quantitative reverse transcriptase–polymerase chain reaction (qRT‐PCR). Receptor associated protein 80 (RAP‐80) ubiquitin interacting motif agarose was used in a pull‐down assay to obtain K 63 ‐polyubiquitinated proteins. Ubiquitin linkages on immunoprecipitated transforming growth factor β–activated kinase 1 (TAK‐1) were analyzed with deubiquitinases. Results: Sharp injury to porcine cartilage caused rapid activation of JNK and NF‐κB pathways and the upstream kinases MKK‐4, IKK, and TAK‐1. Pharmacologic inhibition of TAK‐1 in porcine cartilage abolished JNK and NF‐κB activation and reduced the injury‐dependent inflammatory gene response. High molecular weight species of phosphorylated TAK‐1 were induced by injury, indicating its ubiquitination. An overall increase in K 63 ‐linked polyubiquitination was detected upon injury, and TAK‐1 was specifically linked to K 63 ‐ but not K 48 ‐polyubiquitin chains. In mice, avulsion of wild‐type femoral epiphyses caused similar intracellular signaling that was reduced in cartilage‐specific TAK‐1–null mice. Epiphyseal cartilage of MyD88‐null and TRAF‐6–null mice responded to injury, suggesting the involvement of a ubiquitin E3 ligase other than TRAF‐6. Conclusion: Activation of TAK‐1 by phosphorylation and K 63 ‐linked polyubiquitination by injury indicates its role in driving cell activation. Further studies are needed to identify the upstream ubiquitination mechanisms, including the E3 ligase involved.